Innovative Diagnostic Approaches and Challenges in the Management of HIV: Bridging Basic Science and Clinical Practice - Mohd Afzal; Shagun Agarwal; Rabab H. Elshaikh; Asaad M. A. Babker; Einas Awad Ibrahim Osman; Ranjay Kumar Choudhary; Suresh Jaiswal; Farhana Zahir; Pranav Kumar Prabhakar; Anass M. Abbas; Manar G. Shalabi; Ashok Kumar Sah (Life)
Human Immunodeficiency Virus (HIV) remains a major public health challenge globally. Recent innovations in diagnostic technology have opened new pathways for early detection, ongoing monitoring, and more individualized patient care, yet significant barriers persist in translating these advancements into clinical settings. This review highlights the cutting-edge diagnostic methods emerging from basic science research, including molecular assays, biosensors, and next-generation sequencing, and discusses the practical and logistical challenges involved in their implementation. By analyzing current trends in diagnostic techniques and management strategies, we identify critical gaps and propose integrative approaches to bridge the divide between laboratory innovation and effective clinical application. This work emphasizes the need for comprehensive education, supportive infrastructure, and multi-disciplinary collaborations to enhance the utility of these diagnostic innovations in improving outcomes in patients with HIV.